Removal of Heavy Metals Using Cactus Mucilage and Potato Starch from the Smelter Lagoon in Cerro De Pasco, Peru - E. Quispe Ccanto, E. Pando Castro, R. Torres Romero, B. Vasquez Orihuela, R. Carrasco Soto (Mathematical Statistician and Engineering Applications, 2023)
The present investigation had the objective of evaluating the efficiency of cactus mucilage with potato starch in the removal of Aluminum (Al), Copper (Cu), Iron (Fe), Lead (Pb) and Zinc (Zn). Data were collected from the point with coordinates 361194.863 east and 8809776.548 north of Laguna Smelter, Cerro de Pasco. Initial results were 1.966 mg/L Al; 0.3635 mg/L Cu; 8.844 mg/L Fe; 0.554 mg/L Pb; 1.8563 mg/L Zn. In P1 and with treatment of 50g of cactus mucilage and 10g of potato starch, it was possible to reduce the aforementioned metals, the data obtained are as follows: 1.72 mg/L of Al; 0.28 mg/L of Cu; 6.788 mg/L of Fe; 0.515 mg/L of Pb; 1.5385 mg/L of Zn and also a neutral pH of 7.06 was obtained, therefore an alternative and economic treatment for mining industry water is being proposed.